NOSOCOMIAL INFECTION IN SURGICAL HOSPITAL IN ZAGAZIG UNIVERSITY - E.Y Tohamy; A.A Shaheen; Samah F. El-Awadi (Arab Universities Journal of Agricultural Sciences, 2006)
Surgical site infection (SSI) remains an important cause of morbidity and mortality among hospitalized patients. A total of 254 bacterial isolates were collected from 303 surgical specimens which were isolated from 92 males (53.2%) and 81 females (46.8%), their mean ages were 39.6±16.05 years (ranged from 1 month to 74 years). These isolates were identified as Staphylococcus aureus,Escherichia coli, Klebsiella pneumoniae, Proteus vulgaris, Pseudomonasaeruginosa and commensal Gram+ve and Gram-ve bacteria. The most effective antibiotics were imipenem while ampicillin and penicillin G (First and second generation of b-Lactam) showed much lower activity against all types of bacterial strains. The minimum inhibitory concentrations (MIC) of  imipenem determined by E-test were 0.047- 0.064 , 0.125, 0.19, 0.25 and 0.75mg/ml against Staphylococcus aureus, Escherichia  coli, Proteus vulgaris, Klebsiellapneumoniae  and Pseudomonas aeruginosa  respectively.